Antioxidant activity, total phenolic content, and nutrient composition of Chayote shoot (Sechium edule, Jacq. Swartz) from Kundasang, Sabah: Antioxidant Activity, Total Phenolic Content, and Nutrient Composition of Chayote Shoot (Sechium edule, Jacq. Swartz) from Kundasang, Sabah - Amir Husni Mohd Shariff; Nurrelyssa Azwa Hainusa; Nurul Huda; Mona Zakaria; Saeed Ullah; Fahrul Huyop; Roswanira Abdul Wahab (Journal of Tropical Life Science, 2023)
The chayote (Sechium edule) plant is believed to have significant nutritional importance due to its medicinal functions. It has been widely cultivated in Kundasang, Sabah for vegetable consumption. This study was carried out to determine the health benefits of this vegetable, especially the upper 3-foot of the shoot portion, in terms of antioxidant activity, total phenolic content and nutrient composition. It was divided equally into three parts, each a foot long and classified as: upper tier, middle tier and lower tier and amongst them, which tier gives rise to the best health benefits or will the traditional consumption of the whole 3-foot shoot be better for overall health well-being. DPPH (2,2-diphenyl-1-picryl-hydrazyl-hydrate) and Folin Ciocalteu test were used to determine antioxidant activity and Total Phenolic Content (TPC), respectively. The results showed that the upper tier of shoot parts had the highest value for antioxidant activity, with the lowest of IC50 value (245.12 ± 9.24 μg/ml). The lower part of the plant also shows the highest value for TPC with a value of 355.66 ± 5.84 mg/g GAE. Minerals, Ca, Mg, P, Mo, Fe and Al were the highest value in the middle tier portion. The proximate analyses showed that the upper tier of the shoot has the highest fat, crude protein, and carbohydrate contents. Crude ash has the highest value in the middle tier part. On the other hand, the moisture content and the crude fiber were high at the lower tier of the shoot portion. The upper tier of the shoot is recommended to be consumed for health benefits because it is high in antioxidant activity and proximate content and also rich in minerals. However, the traditional practice is to consume the whole 3-foot long of this vegetable is very welcome